DEVELOPMENT OF INFORMATIVE ENVIRONMENT IS FOR STUDENTS AS MEANS OF INCREASE OF INFORMATIVE COMPETENCE OF TEACHER OF PHYSICS - Sharko, В.Д.; Andreychuk, А.Б. (Journal of Information Technologies in Education (ITE), 2011)
In article ways of increase of level информатической competence of the teacher of physics are defined during working out and use of the information educational environment.